Hazard analysis and critical control point plan for hazards in Ugandan amaranth vegetable value chain - Aber, H.; Mulindwa, J.; Lung'aho, Mercy G.; Nyakundi, Fridah Nyabate; Wambui, J.; Jager, Matthias; Ugen, Michael Adrogu (African Journal of Food, Agriculture, Nutrition and Development, 2019)
Currently, there is a high demand for amaranth due to its ability to withstand harsh climatic conditions, making it an ideal crop in the changing climate. There is also increased awareness and education on its nutritional and overall health benefits, and the availability of improved recipes. However, the presence of hazards can hinder the commercialisation of amaranth, which is in most cases traded informally. Food safety issues along the amaranth value chain should, therefore, be addressed to cope with both production and safety demands. The objective of this study, therefore, was to develop a Hazard Analysis and Critical Control Point (HACCP) plan for hazards in the amaranth value chain in Uganda. The seven principles outlined by Codex Alimentarius were followed to develop the HACCP plan. A tree diagram was further used to identify each potential hazard at each processing stage and Critical Control Points (CCPs) along the chain. For the CCPs identified, reliable control mechanisms and corrective actions were established to fulfil the requirements set by the critical limits to guarantee the safety of the products. Verification and records systems were proposed to determine the effectiveness and traceability of the HACCP plan. For each of the identified CCPs, samples were collected purposively and analysed for chemical and microbial contaminants. From the analysis, fifteen processing stages, starting from the land section to cooking and serving, were identified. Out of these, eight stages were defined as CCPs. These were site selection, land and seedbed preparation, irrigation, market display/humidity control, washing before preparation, chopping, cooking, and holding time and serving. At CCP 1, soils were contaminated with lead and cadmium, mercury and aflatoxins but at considerably low levels. At CCP 2, organic fertilisers were only contaminated with E. coli. At CCP3, E. coli was present in irrigation water. Heavy metals were also present in the irrigation water but were below the critical limits. At CCP4, E. coli was absent in water and display surfaces. E. coli was, however, present on raw amaranth. S. aureus was detected on vendors’ hands. At CCP5, water was not contaminated with E. coli. At CCP6, only personnel hands were infected with S. aureus and Enterobacteriaceae. No contamination was detected in CCP7 and CCP8. Strict control of E. coli in manure and water and S. aureus and Enterobacteriaceae on personnel hands is required to ensure the amaranth value chain attains good food safety output.